Exploring the Strategies and Environmental Factors that Foster Curiosity in Early Childhood Education - Syarif, Siti Hardiyanti; Nisaa, Imamun; Fitriani, Vita (Educia Journal, 2024)
The research investigates the practices which nurture curiosity at early childhood educational levels while analysing actions and physical setups between educators and students in early childhood education spaces. The phenomenological qualitative research design used interviews and document review and observational methods to study 15 educators and 5 administrators and 10 parents. Research findings determined teacher facilitation as the essential component because educators drive curiosity development through their use of questions together with materials and activities and by giving students independence. The discovery revealed that learning zones consisting of physical spaces along with items inside classrooms help students explore and interact with each other. Children from lower SES backgrounds experience difficulties obtaining outside resources for curiosity development since socio-economic influences shape their socio-cultural factors. Inside classroom instruction that uses culture-based materials and teaching methods created favourable conditions which led students to become more interested and focused. This study offers important contributions to existing knowledge through its specific examples of early childhood learning environments which promote curiosity and resolve gaps found in literatures about concrete methodologies and general environmental qualities for early childhood education contexts. Extensive curiosity development needs to consider teachers' practices as well as classroom design and the social influence inside educational settings to be effective.